2018
DOI: 10.1007/s40123-018-0154-6
|View full text |Cite
|
Sign up to set email alerts
|

Near Vision Improvement with the Use of a New Topical Compound for Presbyopia Correction: A Prospective, Consecutive Interventional Non-Comparative Clinical Study

Abstract: Introduction To report the outcomes in near vision, optical quality and pupil diameter of a new pharmacological therapy (FOV tears) for presbyopia. Methods This was a prospective, consecutive, interventional, non-comparative clinical study in which 117 presbyopic patients were given one drop of the novel therapy (FOV tears) in each eye, followed 2 h after the instillation of the eye drop by an evaluation of the binocular uncorrected near visual acuity (UNVA) and uncorre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 16 publications
2
21
0
Order By: Relevance
“…The results of this study shows that near vision improved significantly in all groups 2 h after the instillation of the eye drop. These results correlate with those obtained in our previous studies [ 8 , 9 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of this study shows that near vision improved significantly in all groups 2 h after the instillation of the eye drop. These results correlate with those obtained in our previous studies [ 8 , 9 ].…”
Section: Discussionsupporting
confidence: 93%
“…Some topical treatments have been studied [6][7][8][9][10], reporting an improvement in near vision with the topical application of muscarinic cholinergic agonists. We previously reported our results with a new pharmacological therapy (FOV tears) for presbyopia [8,9]. The aim of this study is to report the near visual outcomes and evaluate the potential of FOV tears in patients with previous corneal refractive surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the ophthalmic formulation combined pilocarpine 0.247%, with the NSAID nepafenac 0.023%, with the addition of phenylephrine (0.78%), pheniramine (0.034%), naphazoline (0.003%), and polyethylene glycol (0.09%). This group has published 2 papers regarding their pharmacological treatment results [32,43]. The first paper, from 2016, by Renna et al, studied the safety and potential efficacy of this ophthalmologic formulation in 14 patients (9 natural emmetropes, 5 stable emmetropes post-LASIK), with an age range of 41-55 years.…”
Section: Restoring Accommodationmentioning
confidence: 99%
“…The second paper, by Vargas et al, in 2019, reported a prospective, consecutive, interventional, noncomparative clinical study on 117 patients with presbyopia, using 1 drop FOV tears (composed of 0.247% pilocarpine, 0.78% phenylephrine, 0.09% OVERVIEW OF PHARMACOLOGICAL TREATMENTS FOR PRESBYOPIA polyethyleneglycol, 0.023% nepafenac, 0.034% pheniramine, and 0.003% naphazoline) in each eye, and assessed UNVA and UDVA 2 hours after instillation of eye drops. The patients were divided into 2 age groups: group 1, aged 41-50 years; and group 2, aged 51-65 years.…”
Section: Restoring Accommodationmentioning
confidence: 99%
See 1 more Smart Citation